THE PORTUGUESE LANGUAGE IN THE REFERENCE MATRIX OF ENEM WRITING: A DECOLONIAL ANALYSIS OF COMPETENCE 1 (TEL Tempo, Espaço e Linguagem, 2022)
The National High School Exam (Enem, brazilian name) is an assessment that aims to assess the performance of graduates from the last stage of basic education. It is also a criterion for admission to higher education. Writing is one of the ways he proposes to evaluate students, having a specific test for this purpose. In this test, one of the criteria of the reference matrix (or correction matrix), indicated by competence 1, is the Portuguese language. Having observed the above, the present study aims to analyze from a decolonial perspective on how this matrix promotes the maintenance of coloniality through language and, as such, levels, hierarchizes and disciplines bodies in favor of establishing a way of conceiving the language.